MINAT BELI MASYARAKAT MELALUI SISTEM ONLINE SHOP PERSPEKTIF EKONOMI ISLAM STUDI PADA MASYARAKAT DESA RIAM MENGELAI KECAMATAN BOYAN TANJUNG KABUPATEN KAPUAS HULU - Akhmad Sahrudin (CV. Adiba Aisha Amira, 2024)
Based on the background of the problem, the researcher formulated several main problems which will be the focus of research in this thesis. The main issues are: 1) what is the public's view of interest in buying through the online shop system in Riam Menglai Village, Boyan Tanjung District, Kapuas Hulu Regency? 2) What are the factors that encourage the buying interest of the people of Riam Menglai Village, Boyan Tanjung District, Kapuas Hulu Regency to buy products online? 3) What is the Islamic economic perspective on the buying interest of the people of Riam Menglai Village, Boyan Tanjung District, Kapuas Hulu Regency through online shops? This research uses a type of qualitative field research method, namely a type of research that qualitatively describes the object being discussed in accordance with the realities found in society. This research uses a case study method. Data collection techniques through interviews, observation and documentation. Data analysis uses an interactive analysis model which includes data reduction, data display and verification/drawing conclusions. The results of this research can be concluded that: 1. People's buying interest through the online shop system in Riam Mengelai Village, that buying interest is driven by various things, such as the application is easy to use, online shopping is not complicated, saves time, saves costs, is commonly used by the community / easy to access, payment can be COD / paid after the goods are received by the buyer, many price variants and many model choices. 2. Factors that encourage people's buying interest in Riam Menglai Village, Boyan Tanjung District, Kapuas Hulu Regency through online shops, namely; the factors of convenience, comfort, effective time and energy in making purchases online, the promotions offered are quite diverse and attractive in online shops such as more and more modern tran models, the price variants provided are quite cheap and easy to reach by the public and payments can be deferred while waiting for the goods arrive or be received by the buyer. 3. From an Islamic economic perspective, doing business online is permitted as long as it complies with the terms of sale and purchase, there is no injustice, elements of usury or fraud.